The onset of the palaeoanthropocene in Iceland: Changes in complex natural systems. (October 2015) - Streeter, Richard; Dugmore, Andrew J; Lawson, Ian T; Erlendsson, Egill; Edwards, Kevin J
Pre-industrial human impacts on the past environment are apparent in different proxy records at different times in different places. Recognizing environmentally transformative human impacts in palaeoenvironmental archives, as opposed to natural variability, is a key challenge in understanding the nature of the transition to the Earth's current 'Anthropocene' condition. Here, we consider the palaeoenvironmental record for Iceland over the past 2.5 ka, both before and after the late ninth century human settlement ( landnám ). The Scandinavian colonization of the island was essentially abrupt, involving thousands of people over a short period. The colonization triggered extensive changes in Icelandic ecosystems and landscapes. A volcanic ash known as the Landnám tephra was deposited over most of Iceland immediately before the settlement began. The Landnám tephra layer thus provides a uniquely precise litho-chrono-stratigraphic marker of colonization. We utilize this marker horizon as an independent definition of the effective onset of the local palaeoanthropocene (which is conceptually related to, but distinct from, the global Anthropocene). This allows us to evaluate proxy records for human impact on the Icelandic environment and to assess how and when they show transformative impact. Based on this analysis, we consider the implications for understanding and defining the Anthropocene in those areas of the Earth where such a clear independent marker of the onset of significant human impacts is lacking.